first : distribute the 3 into the bracket on th e right hand side post your answer here
4 - t = 3t - 3 - 5
OK good - now tidy up the right side by completing the subtraction
4 - t = 3t - 8
4-t=3[t-1]-5 4-t=3t-3-5 4-t=3t-8 4+8=3t-t 12=2t t=6
@ trentren you should not thank him giving you the answer REALLY does not teach you anything - and YOU are the one who needs to know haw to do it - not him
he went step by step with it though.
can YOU do a similar question by yourself? 3-2t= 3(t-1)-8
14 = 5t
is that the answer?
14=5t is correct the other answer is not